KNOWLEDGE IMPROVEMENT OF NUTRITION AND ENGLISH IN SCHOOL-AGE CHILDREN IN THE COVID-19 PANDEMIC ERA: PENINGKATAN PENGETAHUAN GIZI DAN BAHASA INGGRIS PADA ANAK USIA SEKOLAH PADA ERA PANDEMI COVID-19 - Komala, Ramadhana; Febriani, Wiwi (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: The existence of the Covid-19 pandemic has an impact on a learning crisis in children. More than 120 countries have implemented social interaction violations through school closures which have affected 1.6 million students worldwide spread across 166 countries, including Indonesia. Purpose: This community service activity aims to improve the knowledge of School-Age Children (SAC) about nutrition combined with learning English during the Covid-19 Pandemic era. Method: This activity was carried out in six meetings from January 19 to February 6 2021, in Wonokriyo Village, Gading Rejo District, Pringsewu Regency, Lampung. The target of this activity is 24 SAC took class 4-6. Students are given nutrition counseling using the lecture method using various media including booklets, power points, and educational games. Student knowledge data were obtained from pre-test and post-test questionnaires. The data analysis performed was univariate data and the proportion of knowledge increase. Results: The average age of the respondents was 10.5 ± 0.9 years, the majority were female and took class IV of elementary school. The highest average increase in children's nutritional knowledge on the topic tumpeng of balanced nutrition was 45.3 ± 13.6 points from 38.7 ± 10.9 points to 84.0 ± 9.5 points. The average knowledge of children's English also increased from 41.0 ± 10.4 points to 78.0 ± 6.8 points with an average change of 37 ± 9.0 points. Conclusion: Nutrition counseling that is integrated with learning English can increase children's knowledge related to nutrition and English.